Razvoj geografije v srednjem veku - Ogrin, Darko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2018)
The paper presents the history of geography in the Middle Ages through the findings in Slovenian and foreign literature. The Middle Ages were not a uniform period as regards the development of geography. The Early Middle Ages were marked by the decline of Classical Antiquity traditions in the Christian part of Europe on the one hand, but on the other hand they were accepted and upgraded in the Islamic world. In the High Middle Ages, Islamic findings formed the basis for geographic and cartographic renaissance and for the development in the following centuries
Keywords: geografija; srednji vek; zgodovinski pregledi